The Disconnection of Identity and Place in Drawing: Superficial Exploration of Cultural Landscapes (American Journal of Arts and Human Science, 2024)
This art-based research explores the disconnect between personal identity and sense of place when representing cultural landscapes through superficial drawing practices. Existing solely as visual representations focused on formal qualities of form and colour, drawings of cultural landscapes often fail to deeply engage with the lived experiences, histories, and meanings embedded within those places. Through a series of plein-air drawings created in three distinct cultural landscapes-a rural farming community, an urban park, and a historical heritage site-this research examines how superficial approaches to landscape drawing can distance the artist from genuinely understanding and connecting to the places depicted. Drawings were analysed using contemplative art criticism to evaluate how effectively they conveyed embedded cultural meanings and perspectives beyond mere visual documentation. The findings suggest that without contextual research into the landscapes’ social and cultural significance and reflective practices connecting the artist’s identity and experiences to the place, the drawings became detached representations lacking depth of meaning. This superficial approach resulted in a disconnection between the artist’s sense of identity and place in the depicted landscapes. To more authentically connect representation to meaning, the researcher proposes an alternative model for cultural landscape drawing that emphasizes experience-based practices and reflective inquiry into the intersections between artist, place, and community identities. Such an approach holds potential to bridge divisions between external visualization and internal comprehension of what cultural landscapes signify on deeper levels.